2009
DOI: 10.1177/1941738109347775
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Single-Blinded Comparison of Stretching Versus Stretching and Joint Mobilization for Posterior Shoulder Tightness Measured by Internal Rotation Motion Loss

Abstract: Background:Posterior shoulder tightness, as demonstrated by limited internal rotation range of motion, is a suggested factor in many shoulder pathologies. Methods to increase posterior shoulder mobility may be beneficial.Hypothesis:Shoulder internal rotation range of motion will not change with either of 2 interventions: cross-body stretch alone and cross-body stretch plus posterior capsule joint mobilization.Study Design:Randomized controlled single-blinded clinical trial.Methods:The study comprised 39 colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
104
3
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 35 publications
(78 reference statements)
5
104
3
2
Order By: Relevance
“…This is of particular importance when improvements in ROM are sought within asymptomatic individuals. Indeed, many researchers have demonstrated ROM improvements at various joints following accessory mobilisation treatments in asymptomatic individuals (MacRae et al, 2012;Manske et al, 2010;McCollam & Benson, 1993;Thomson et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…This is of particular importance when improvements in ROM are sought within asymptomatic individuals. Indeed, many researchers have demonstrated ROM improvements at various joints following accessory mobilisation treatments in asymptomatic individuals (MacRae et al, 2012;Manske et al, 2010;McCollam & Benson, 1993;Thomson et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…9,10,33,37,42 Furthermore, posterior glenohumeral soft tissue tightness has been identified as a cause of restricted glenohumeral IR. 7,13,14,18,23,25,27,30,33,37,39,42 Thus assessment of IR ROM is a critical t stuDY DesiGn: Clinical measurement, reliability.…”
mentioning
confidence: 99%
“…4, 21 Tyler et al 21 reported that the cross-body stretch, or horizontal adduction stretch, also improved shoulder IR. In addition, Manske et al 12 reported that combining horizontal adduction stretching exercises with posteriorly directed glenohumeral joint mobilization techniques increased shoulder IR. Cadaveric studies designed to determine the best position to stretch the posterior shoulder soft tissue structures have quantified the strain on the posterior cuff and capsule in a number of positions.…”
Section: Stretching Techniquesmentioning
confidence: 99%
“…McClure et al 13 reported a significantly greater increase in IR using the cross-body stretch as compared to the sleeper stretch. Manske et al 12 reported that subjects treated …”
Section: Stretching Techniquesmentioning
confidence: 99%